The expression of microrna-744 (MIR-744) in nasopharyngeal carcinoma: a preliminary study - Othman, Noor Syarmila; Leman, Wan Ishlah; Abdullah, Kahairi; Muhammad, Siti Aeshah @ Naznin; Kaderi, Mohd Arifin (IIUM Press, International Islamic University Malaysia, 2018)
The aim of this study was to investigate the level of miR-744 expression in nasopharyngeal carcinoma (NPC) tumour tissue and to provide initial clue on its potential as biomarkers for early detection of NPC in a preliminary analysis. Total miRNAs was extracted from NPC tissue as well as normal nasopharynx tissue taken from Hospital Tengku Ampuan Afzan (HTAA), Kuantan and converted into cDNA. The level of miR-744 expression in the cDNA was quantified using quantitative reverse transcription polymserase chain reaction (RT-qPCR) technique. The expression level of SNORD48 was measured simultaneously for each sample, which served as endogenous control. The difference in the expression of miR-744 in NPC and normal nasopharynx tissue were analysed using relative quantification, 2-ΔΔCT. In this preliminary analysis, this study found that miR-744 was upregulated in NPC as compared to normal nasopharynx tissue by 2.5 fold changes, respectively suggesting it may involve in progression of tumour. However, the finding is not significant and may not accurately reflect the overall population, due to small sample size involved in the study. Findings from the current study suggest the potential of miR-744 to serve as useful diagnostic and prognostic biomarker in NPC.